1984
DOI: 10.1007/bf02302551
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of proteinaceous substances in the estuary of the Tama River

Abstract: Behaviour of dissolved and particulate proteinaceous substances in the estuary of the Tama River was investigated through field observations and laboratory experiments. Concentrations of dissolved proteinaceous substances in estuarine water were determined at eight stations between the mouth of the Tama River (TA-I5) and a point 16 km upstream (TA-8), using the colorimetric method of Lowry et al. (195i) that employs Folin phenol reagent. The results were expressed in terms of Folin phenol active substances (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Estuaries act as filters of land-based chemicals to the ocean. It has been found that various land-derived materials are removed in estuaries through flocculation (39)(40)(41)(42), uptake by phytoplankton (43), and biodegradation (19). The application of FWAs as molecular markers in the marine environment requires their survival in estuaries.…”
Section: Reported Steady-state Isomeric Compositions: [Ez]-dsbp ) 16-...mentioning
confidence: 99%
“…Estuaries act as filters of land-based chemicals to the ocean. It has been found that various land-derived materials are removed in estuaries through flocculation (39)(40)(41)(42), uptake by phytoplankton (43), and biodegradation (19). The application of FWAs as molecular markers in the marine environment requires their survival in estuaries.…”
Section: Reported Steady-state Isomeric Compositions: [Ez]-dsbp ) 16-...mentioning
confidence: 99%